Trust and Reputation under Asymmetric Information - Moritz Janas; Emilia Oljemark (ZBW - Leibniz Information Centre for Economics, 2020)
We study the role of information about the multiplier in a finitely repeated investment game. A high multiplier increases the reputational incentives of a trustee, leading to more repayments. Our perfect Bayesian equilibrium analysis shows that if the trustee is privately informed about the multiplier, both the expected frequency of investments and repayments as well as the expected payoffs of both players are higher compared to a situation where the multiplier is public knowledge. We test this result in a laboratory experiment. The data cannot confirm the predicted welfare dominance of private information about the multiplier. We discuss potential reasons for the deviation between theory and experimental data.
Keywords: C73; C92; D82; D83; M13; 330; reputation; trust; incomplete information; experiment